Effect Of Product, Distribution And Service Quality on Customer Loyalty Through Customer Satisfaction At Indonesian Marketplace - Andri, Primadi; Jasfar, Farida; Kristaung, Robert (Green Publisher, 2022)
Since in online business must involve a reliable marketing strategy to be able to compete in cyberspace to satisfie and growing customers’ loyalty when the transaction is done without meeting face to face with prospective customers or see the product in person. The objectives of this research are (1) to analyze the relationship of positive product quality, distribution, service quality, on customer loyalty. And the relationship of positive product quality, distribution and service quality on customer loyalty through customer satisfaction simultaneously; (2) to identify the factors that influence customers to choose a marketplace in Indonesia; (3) to analyze the needs and expectations of early consumers. This research was conducted using a survey method. Data were collected using a questionnaire tool with Structural Equation Modeling (SEM) analysis. The sampling technique used the purposive sampling method by taking 400 respondents from the top five marketplace customers in Indonesia. The results indicate that the number of visits and online transactions in the top five marketplaces in Indonesia has changed from previous research data. There is no significant effect of product quality on customer loyalty. However, after re-testing by removing outlier data, there is a significant positive effect of product quality on loyal customers. There is a significant effect of product quality and service quality on customer satisfaction. There is no significant effect of distribution on customer loyalty and customer satisfaction. In addition, there is a significant effect of service quality and customer satisfaction on customer loyalty.